Critical Minerals in the Context of Canada: Concepts, Challenges and Contradictions - Kerr, Andrew (Geoscience Canada, 2023)
Increased use of renewable energy, coupled with electrification of the economy, is considered important in efforts to limit future climate change. This energy transition is predicted to increase demands for some commodities, many of which are now labelled as critical mineral. The quest for such commodities is now a persistent theme for the resource industry and emerging government policies. This review for non-specialists explains several key concepts but also explores some challenges and apparent contradictions in the context of Canada.Canada now has a list of 31 critical minerals, but this includes some major commodities for which domestic production is significant and supply risk is low. The differences between our list and those of other jurisdictions reflect our more specific definitions. Most other commodities on Canada’s list are also identified by other countries and some are specifically linked to the energy transition. These include cobalt, lithium, manganese, nickel, graphite and vanadium (used in electric vehicle batteries and static energy storage), rare earth elements (REE; used for magnets in EV motors and wind turbines) and some rarer elements (e.g. germanium, gallium, indium and tellurium) used in photovoltaic (solar) energy systems. Some of these are potential primary products (e.g. lithium, graphite and REE) but many others (e.g. cobalt, platinum group elements and the photovoltaic elements) are byproducts from the production of major commodities, notably nickel, copper and zinc. The REE represent coproducts that are closely associated in nature and very hard to separate from each other; they are produced as a group.There are some specific challenges in exploring for and developing critical mineral resources. The end-use technology driving demand evolves on a timescale of years, but mineral exploration and development now typically take multiple decades. Material substitutions and unpredictable developments in technology complicate the exact prediction of future demands. The forecasts of overall relative demand growth are impressive, but for some key commodities global production will remain small in absolute terms, which may limit the potential for new discoveries. Simple measures of grade and tonnage are not always guarantees of viability, because deposits of some commodities (e.g. the REE) are mineralogically complex. Byproduct commodities cannot be produced in isolation, and many of these are only extracted in smelting and refining. Domestic production of these commodities is effectively lost if concentrates are exported for processing. The emissions and environmental impacts associated with production of critical mineral resources will also become important if such activity is to be linked to wider climate goals. This may present challenges in northern Canada, where renewable or low-carbon energy options are limited. Most draft Land Use Plans in the north presently emphasize large-scale land conservation, which could limit future exploration access before resource potential is fully assessed. Given the strong divisions of opinion about resource development, especially in the north, controversy and polarized debate will not easily be avoided.There are no simple answers to challenges that are political or jurisdictional rather than technical, but there is definitely a need for more public geoscientific information. This will help to identify areas of greatest potential, evaluate known deposits and contribute to future sustainable development. For many of the commodities on our critical mineral resources list, data for Canada remains incomplete, especially in more remote regions that are generally considered to have the highest potential.